Um estudo sobre a atmosfera de planetas rochosos: uma contribuição para o letramento científico por meio da Astronomia de estudantes do 1º ano do Ensino Médio - Santos, Gilvan Gomes dos (2025)
This exploratory research with a qualitative approach supported by descriptive analysis of simple quantitative data analyzed the atmospheres of Mercury, Venus, Earth and Mars to develop Scientific Literacy in 171 students in the 1st year of SESI José Carvalho High School in Feira de Santana, BA. We used Gamification, Questionnaires, Audiovisual Resources and Production of Scientific Scripts to produce our Educational Product, the Didactics Sequence, which was applied and showed that the students understood the different processes of atmospheric formation of the rocky planets and were able to relate Earth's climate changes to anthropic action and greenhouse gas emissions, demonstrating significant progress in scientific learning.